2021
DOI: 10.3390/pr9061008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Antimicrobial Activity and Docking Study of Vanadium Mixed Ligand Complexes Containing 4-Amino-5-hydrazinyl-4H-1,2,4-triazole-3-thiol and Aminophenol Derivatives

Abstract: The synthesis of mixed-ligand complexes is considered an important strategy for developing new metal complexes of enhanced biological activity. This paper presents the synthesis, characterization, in vitro antimicrobial assessment, and theoretical molecular docking evaluation for synthesized oxidovanadium (V) complexes. The proposed structures of the synthesized compounds were proved using elemental and different spectroscopic analysis. The antimicrobial tests showed moderate activity of the compounds against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…indicated promising stabilization efficiency and η displayed low ability transformation of electronic‐current to distortion direction [39] . It has been reported that low IP indicates good anticancer efficiency [38] . It can be observed that compounds 7 – 17 possess low (IP=0.202 to 0.206 au.)…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…indicated promising stabilization efficiency and η displayed low ability transformation of electronic‐current to distortion direction [39] . It has been reported that low IP indicates good anticancer efficiency [38] . It can be observed that compounds 7 – 17 possess low (IP=0.202 to 0.206 au.)…”
Section: Resultsmentioning
confidence: 98%
“…The calculated descriptors for all the molecules and the reported biomaterials values were harmonized [38] and are listed in table 3. The low ΔE =−0.058 to −0.168 au.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the relationship between the biological findings in vitro and the interaction affinities of the investigated hybrids, the docking analysis of the most active derivatives, 2 , 4 and 6 , was assessed to identify their binding mode inside the (PDB: 1DLS) [ 40 ] and DNA gyrase (PDB; 4uro [ 41 , 42 , 43 ]) active sites, as well as the structural orientation and conformation. The docking steps were applied as in a previously reported method [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The weak stretching bands of the ligands, L 1, and L 2 , were observed at 2555 cm −1 and 2557 cm -1 respectively due to ν(S−H) group disappearing in both the vanadium complexes confirming the participation of sulfur atom in complexation by deprotonation. It is clearly observed that these two weak bands due to the thiol group (−SH) and other two bands due to the thione group (C=S) at 1062 and 1060 cm -1 for respective ligands, seen in IR spectra of both the ligands illustrate the thione-thiol tautomerism of the Schiff bases [5,15]. The weak and broad band observed at ~(3387−3236) cm −1 range could be assigned to the stretching vibrations of the O−H group.…”
Section: Vibrational Spectramentioning
confidence: 96%
“…In recent years, important metal chelators, Schiff bases and their numerous forms, are being discovered for the treatment of diseases like bacterial, fungal, and viral infections, tuberculosis, tumor, etc. [4,5]. The study of chemistry and biological performances of the vanadium complexes with different chelators and complexation agents by changing their substituting functional groups have added novelty to this type of research.…”
Section: Introductionmentioning
confidence: 99%